Lexical loans from Quechua and Spanish in Asháninka - Alonzo Sutta, Alicia (2014)
In this work we will show some lexical elements of the Quechua language that are found in the Ashaninka vocabulary. Due to the fact that this study may be one of the first approximations to the linguistic contact phenomenon between Quechua and Ashaninka, it won’t be specified which dialect of Quechua produced such linguistic contact. The lexical elements waripa, sonqo, and ashka from the Quechua language would have been incorporated into the Ashaninka vocabulary as linguistic adoptions. Furthermore, the contact between Ashaninka and Spanish in more recent times would have made possible the borrowing from Ashaninka to Spanish. For example, words such as “sable” and “cuchillo” would have its origins in the Ashaninka words “sabiri” and “kotsiro”.